Sources and effects of ionizing radiation. UNSCEAR 2008 Report to the General Assembly. Volume I (New York, 2010)
"Exposure to radiation has origins such as medical diagnosis and therapeutic procedures; nuclear weapons production and testing; as well as occupations that entail increased exposure to artificial or naturally occurring sources of radiation. Since the establishment on of the United Nations Scientific Committee on the Effect of Atomic Radiation the mandate of the committee has been to undertake board reviews of the sources of ionizing radiation and of the effects of that radiation on human health and the environment. The committee last made estimates of radiation levels and trends in its 2000 report. The present report updates and extends those estimates."